Comparative transcriptome responses of leaf and root tissues to salt stress in wheat strains with different salinity tolerances - Li, Jianfeng; Gao, Xin; Chen, Xunji; Fan, Zheru; Zhang, Yueqiang; Wang, Zhong; Shi, Jia; Wang, Chunsheng; Zhang, Hongzhi; Wang, Lihong; Zhao, Qi (Frontiers in Genetics, 2023)
Background: Salinity stress is one of the major adverse environmental factors which can limit crop yield and restrict the normal usage of land. Selection of salt-tolerant strains and deciphering the underlying mechanisms are urgent for plant breeding scientists to increase agricultural production in arid and semi-arid regions. Results: In this study, we selected salt-tolerant wheat (Triticum aestivum), ST9644, and used it as the model to study the difference in expression pattern between salt-tolerant and salt-sensitive strains. High throughput RNA sequencing resulted in more than 359.10 Gb clean data in 54 samples, with an average of 6.65Gb. Besides the IWGSC reference annotation, we found 50,096 new genes, 32,923 of which have function annotation. Comparison of abundances between salt-tolerant and salt-sensitive strains showed that there are 3,755, 5,504 and 4,344 genes differentially expressed at 0h, 6h and 24h respectively in root tissue under salt stress. KEGG pathway analysis for these genes showed that they were enriched in Phenylpropanoid biosynthesis (ko00940), Cysteine and methionine metabolism (ko00270) and Glutathione metabolism (ko00480). Besides, we also used WGCNA analysis to find the time course of root tissue’s response to salt stress and found the acute response lasts over 6h and ends before 12h. We also found some key alternative splicing factors showing different splicing patterns in salt -sensitive and salt-tolerant strains, but only few of them were differentially expressed in the two groups. Conclusion: Our results in this study can offer a better understanding for wheat salt-tolerant and improve the wheat breeding process.